Square-Wave Voltammetric Determination of Antihistaminic Drug Hydroxyzine in Pharmaceuticals Using a Boron-doped Diamond Electrode - Scremin, Jessica (Orbital: The Electronic Journal of Chemistry, 2016)
The determination of antihistaminic hydroxyzine using square-wave voltammetry and a cathodically pretreated boron-doped diamond electrode is described. The obtained analytical curve was linear in the hydroxyzine concentration range 0.50 – 20.0 mmol L–1 in 0.1 mol L–1 HCl solution, with a detection limit of 0.43 mmol L–1. Addition and recovery studies in commercial tables and liquid formulations showed excellent recovery values ranging from 94.3 % to 104 %. Furthermore, the proposed method was successfully applied in the determination of hydroxyzine in several pharmaceutical formulations and the results were in a close agreement at a 95 % confidence level with those obtained using an official potentiometric method. DOI: http://dx.doi.org/10.17807/orbital.v8i3.833